Climate Change Impacts on Plant Phenology: Grapevine (Vitis vinifera) Bud Break in Wintertime in Southern Italy - Daniel Grigorie Dinu (MDPI AG, 2021)
The effects of global warming on plants are not limited to the exacerbation of summer stresses; they could also induce dormancy dysfunctions. In January 2020, a bud break was observed in an old poly-varietal vineyard. Meteorological data elaboration of the 1951–2020 period confirmed the general climatic warming of the area and highlighted the particular high temperatures of the last winter. Phenological records appeared to be significantly correlated to wood hydration and starch reserve consumption, demonstrating a systemic response of the plant to the warm conditions. The eight cultivars, identified by single-nucleotide polymorphism (SNP) profiles and ampelographic description, grown in this vineyard showed different behaviors. Among them, the neglected Sprino, Baresana, Bianco Palmento, and Uva Gerusalemme, as well as the interspecific hybrid Seyve Villard 12.375, appeared to be the most interesting. Among the adaptation strategies to climate changes, the cultivar selection should be considered a priority, as it reduces the inputs required for the plant management over the entire life cycle of the vineyard. Hot Mediterranean areas, such as Salento, are a battlefront against the climate change impacts, and, thus, they represent a precious source of biodiversity for viticulture.